PEMBENTUKAN KARAKTER RELIGIUS MELALUI KEGIATAN MENTORING DI MI MA’ARIF NU SUKODADI LAMONGAN - Shoimah, Retno (Jurnal Primary (Kajian Ilmu Pendidikan Dasar dan Humaniora), 2023)
Abstract This study aims to (1) To explain the implementation of Religious Character Building through Mentoring Activities at MI Ma’arif NU Sukodadi (2) Describe the religious character of students at MI Ma’arif NU Sukodadi, after participating in mentoring activities. This research is descriptive, using data collection methods in the form of interviews, observations, and documentation. And data analysis techniques use data reduction, data presentation, and drawing conclusions. The conditions for the implementation of mentoring activities at MI Ma’arif NU Sukodadi went well. This can be seen in the good planning, the material presented is related to islamic values contained in the book of Ta'lim Muta'allim and Nashoihul Ibad, competent mentors. The process of building religious character through mentoring activities is carried out using habituation methods, exemplary methods, story methods and motivation.So, students can increase their faith and devotion to Allah, the formation of akhlaqul karimah, increasing students knowledge about islam. Keywords: Religious character building, mentoring activities